Influence of planting dates, plant density, organic amendments and sanitation on downy mildew of blond psyllium - V.N. PATHAK, B.S. RATHORE and (Indian Phytopathology, 2002)
Experiments were conducted during rebl 1991-92 to 1996-97 to ascertain effect of sowing dates, plant population, role of organic amendments and sanitation on downy mildew of blond psyllium (Plantago ovata Forsk) caused by Peronospora alta Fuckel. Studies revealed that as the sowing of the crop delayed from October 15 onwards, time required for initiation of disease symptoms also reduced. The crop sown on all the five dates produced systemically infected plants, however minimum incidence (7-8%) recorded when crop was sown on October 15. Incidence of systemically infected plants increased with the increase in plant population. Minimum incidence (15.6%) was in the treatment with the lowest plant population (3 lakh/ha). Non significant interaction was observed with different combinations of date of sowing and plant population with regard to percent disease incidence of systemic infection. The crop sown on all the five dates showed non-systemically infected plants, however minimum disease intensity (10-15%) of non-systemic infection was recorded in December 15 sowing. The percent disease intensity (POI) of non-systemic infection increased significantly with increasing plant population. There was a significant interaction between different dates and plant population with regard to POI. Minimum POI (4.5%) was recorded in the crop sown on December 15 combined with the lowest plant density (3 lakh/ha). A continuous and significant reduction in seed yield was recorded when the crop was sown on October 15 and onwards. There was a significant interaction between different dates of sowing and plant population with regard to seed yield. The highest seed yield (1271 kg/ha) was obtained by sowing the crop on October 15 with 3 lakh plants per hectare. Among the organic amendments lowest incidence of systemic infection (14%) and POI of non-systemic infection (33.4 to 34.2%) and highest seed yield (674-738 kg/ha) was recorded in plots amended with farm yard mannure. Oospores of pathogen lost viability/infectivity over the years and could remain viable and infective in seeds and debris at least for five years.